LSO:Ce Inorganic Scintillators Are Biocompatible With Neuronal and Circuit Function - Bartley, Aundrea F.; Abiraman, Kavitha; Stewart, Luke T.; Hossain, Mohammed Iqbal; Gahan, David M.; Kamath, Abhishek V.; Burdette, Mary K.; Andrabe, Shaida; Foulger, Stephen H.; McMahon, Lori L.; Dobrunz, Lynn E. (Frontiers in Synaptic Neuroscience, 2019)
Optogenetics is widely used in neuroscience to control neural circuits. However, non-invasive methods for light delivery in brain are needed to avoid physical damage caused by current methods. One potential strategy could employ x-ray activation of radioluminescent particles (RPLs), enabling localized light generation within the brain. RPLs composed of inorganic scintillators can emit light at various wavelengths depending upon composition. Cerium doped lutetium oxyorthosilicate (LSO:Ce), an inorganic scintillator that emits blue light in response to x-ray or UV stimulation, could potentially be used to control neural circuits through activation of channelrhodopsin-2 (ChR2), a light-gated cation channel. Whether inorganic scintillators themselves negatively impact neuronal processes and synaptic function is unknown, and was investigated here using cellular, molecular, and electrophysiological approaches. As proof of principle, we applied UV stimulation to 4 µm LSO:Ce particles during whole-cell recording of CA1 pyramidal cells in acute hippocampal slices from mice that expressed ChR2 in glutamatergic neurons. We observed an increase in frequency and amplitude of spontaneous excitatory postsynaptic currents (EPSCs), indicating activation of ChR2 and excitation of neurons. Importantly, LSO:Ce particles did not affect survival of primary mouse cortical neurons, even after 24 hours of exposure. In extracellular dendritic field potential recordings, no change in the strength of basal glutamatergic transmission was observed during exposure to LSO:Ce microparticles. However, the amplitude of the fiber volley was slightly reduced with high stimulation. Additionally, there was a slight decrease in the frequency of spontaneous EPSCs in whole-cell voltage-clamp recordings from CA1 pyramidal cells, with no change in current amplitudes. The amplitude and frequency of spontaneous inhibitory postsynaptic currents were unchanged. Finally, long term potentiation, a synaptic modification believed to underlie learning and memory and a robust measure of synaptic integrity, was successfully induced, although the magnitude was slightly reduced. Together, these results show LSO:Ce particles are biocompatible even though there are modest effects on baseline synaptic function and long-term synaptic plasticity. Importantly, we show that light emitted from LSO:Ce particles is able to activate ChR2 and modify synaptic function. Therefore, LSO:Ce inorganic scintillators are potentially viable for use as a new light delivery system for optogenetics.